Prose models - Levin, Gerald (Harcourt Brace Jovanovich, 1975)
The book introduces students to rhetorical and logical ideas in prose composition through the analysis of prose models. The selections are both models of good writing and interesting discussions of important ideas. The book progresses from part to whole. It begins with such topics as emphasis, coordination and subordination of ideas, and climax in the paragraph and sentence, and moves to their use in the whole essay.